Cleartextualism and Sexualism - Harry (Tzvi) Naftalowitz (Washington University Global Studies Law Review, 2022)
The Supreme Court’s landmark opinion of Bostock v. Clayton County is now loved and loathed for its broad protection of homosexual employees from employment discrimination. Equally important to the legal scholar is Bostock’s approach to statutory interpretation. This article seeks to analyze Bostock’s use of textualism through the lens of comparative law. A review of the relevant cases and statutes worldwide suggests that, unlike Bostock, “sex” does not include an individual’s sexual orientation.